LEVY REVENUE PERFORMANCE REGIONAL GENERAL HOSPITAL Dr. AGOESDJAM KETAPANG - ME, Hairani (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT This thesis discusses the performance analysis of hospital admission fees Dr.Agoesdjam as public sector status BLUD using the Value for Money and a modified typology Klassen. Purpose of this study was to analyze the level of Economics, Efficiency and Effectiveness of hospital management Retribution Dr.Agoesdjam Ketapang, knowing how big contribution to the levy, and the levy to know where to position the hospital to Ketapang retribution. This research is expected to be used as a guideline in setting the revenue target derived from levies hospitals, the data used in this study is secondary data is data obtained from the study of literature in the form of records, reports and documents related to the subject and object of research on dr . Agoesdjam Ketapang District, Ketapang District Revenue Office, Finance Department Secretariat Ketapang District for 7 years, which was in 2005-2011. Analysis tool used is the contribution levy Hospital, Economical, Efesinsi and Effectiveness. Based on this research, contribution levy receipts Dr.Agoesdjam Ketapang District Hospital for 7 years ie 2005-2011 to Retribution year average of 93.87%, while the level of financial performance assessments economic perspective shows that financial management is not economical with average average of 97.52% (X <100%) did not achieve the set targets, the level of efficiency of management shows that inefficient with an average of 500.39% (X> 100%), while the level of effectiveness of the levy based hospitals Dr.Agoesdjam a potential revenue base levies are levies Inpatient, Outpatient and Emergency Unit is based on the analysis of the effectiveness of retribution Hospital 2005-2011 obtained Dr.Agoesdjam Ketapang is an average of 101.27% or (X> 100%) This indicates that the level of effectiveness of the levy can be categorized effectively Dr.Agoesdjam Hospital.